Tire friction on ice : development of testrig and roughness measurement method - Wennström, Joakim (2007)
This master thesis is an introduction of a research project at Luleå University of Technology regarding tire friction during winter conditions. The purpose of the research project is to improve the understanding of the tribology in a tire and road contact during winter conditions and also facilitate winter testing of automotives. This thesis describes the mechanisms involved during friction generation under summer conditions. Based on this theory it is concluded that surface roughness is important for friction generation. Therefore, the thesis is aimed towards the roughness of ice and its effect on friction between tire and ice. Two tools are developed that are supposed to be used in conjunction with experiments to investigate if and how roughness of an ice surface contributes to generation of friction in a tire and ice contact. The first tool is a technique to make a replica of an ice surface and then measure the topography of the replica using an interferometer. Some evaluation of the measurement method is done and the method is promising. The second tool is a test rig for measuring of the friction between a rubber wheel and an ice surface. It consists of a rail with a rubber wheel connected to it. The wheel is translated along the rail and the wheel will roll on the ground surface. Braking torque is applied to the wheel and torque and slip rate is measured. The test rig is supposed to be used in controlled laboratory conditions on an artificially made ice surface. The rubber wheel is a solid, truck tire compound, rubber ring with a diameter of 79 mm. During the braking sequence, torque and sliprate is measured and logged. The normal force and translation speed can be varied between 20 – 100 N and 0 – 1 m/s respectively. Description, technical data and a user’s guide for the rig is included in the thesis. Validerat; 20101217 (root)